Burkholderia cepacia lipase immobilized on heterofunctional magnetic nanoparticles and its application in biodiesel synthesis. Issue 1 (December 2017) - Li, Kai; Fan, Yanli; He, Yaojia; Zeng, Leping; Han, Xiaotao; Yan, Yunjun
Abstract Biodiesel production using immobilized lipase as a biocatalyst is a promising process. The performance of immobilized lipase is mainly determined by supporting materials and immobilization method. To avoid the shortcomings of adsorption and covalent bonding methods, in this study, we developed a novel heterofunctional carrier of being strengthened anion exchange and weakened covalent binding to avoid activity loss and improve operational stability of the immobilized lipase. 2, 3-epoxypropyltrimethylammonium chloride with epoxy and quaternary ammonium group and glutaraldehyde were grafted onto aminated magnetic nanoparticles (AMNPs) to generate a new matrix, named GEAMNP. ThenBurkholderia cepacia lipase (BCL) was immobilized on GEAMNP via anion exchange and covalent bonding. The transesterification between soybean oil and methanol was used to test the activities. Activity recovery of the immobilized BCL was up to 147.4% and the corresponding transesterification activity was 1.5-fold than that of BCL powder. The immobilized lipase was further used for biodiesel production to confirm its feasibility. The fatty acid methyl esters conversion yield could reach 96.8% in the first 12 h. Furthermore, the immobilized lipase, BCL-GEAMNP showed markedly improved operational stability, better reusability and higher esters than BCL-GAMNP, where MNPs were only modified with (3-aminopropyl) triethoxysilane and glutaraldehyde.